Effect of Village Fund Financial Management on Financial Performance: Mediating Role of Community Participation - Martha Racwel Patty (West Science Interdisciplinary Studies, 2026)
Village fund management is a crucial factor in determining village financial performance, but empirical findings related to this relationship still show inconsistent results, particularly regarding the role of community participation. This study aims to analyze the effect of Village Fund financial management on village financial performance by considering the mediating role of community participation. The study uses a quantitative approach with an explanatory research design and was conducted in 19 villages in Taniwel Subdistrict, West Seram Regency. Primary data were collected through structured questionnaires administered to village officials directly involved in village financial management and analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM). The results show that Village Fund financial management has a positive and significant effect on village financial performance. In addition, transparent and accountable financial management has been shown to significantly increase community participation. Community participation also has a positive effect on village financial performance and acts as a mediating variable that strengthens the influence of financial management on village financial performance. These findings confirm that improving village financial performance requires synergy between the quality of financial management and active community involvement, especially in the context of villages in Taniwel Subdistrict.